Motivations of inter vivos transfers among Malaysian Muslims - Suhaili Alma’amun; Mohd Khairy Kamarudin; Mehmet Asutay (Danubius University, 2016)
The surge of interest in inter vivos transfers has sparked a debate over its motivations. However, most of the academic research has focused on developed economies; and similar to many other countries, empirical research is scarce in Malaysia too. This study, aims to unravel motives for inter vivos transfers among Malaysian Muslims. It employs logit regression analysis in which the data is collected by means of questionnaires from October to December 2012.This research discovers that exchange motive is more prevailing than altruism motive among the respondents. More inter vivos transfers are given to daughters, children who provide more services and children with low opportunity cost of their time. However, inter vivos gifts among Muslims in Malaysia have one distinctive feature, they have been a part of the Malay culturally defined sphere enriched by the Islamic law. This is called „hibah‟ in Malay language, which originates from an Arabic word. It is concluded that the cultural aspect of the inter vivos transfers provides enhanced information as to how the transfer mechanism work.